Atividades de baixo impacto e uso antrópico consolidado previstos no novo código florestal brasileiro (Lei nº 12.651/12) - Laudares, Sarita Soraia de Alcântara (2014)
The Permanent Preservation Areas (APP) and Legal Reserve (RL) were established by rule of law in Brazil (Law n° 4.771/65) because of their ecological importance and supply of environmental goods and services to humans. However, despite the need for protection they still suffer with the human intervention process in agriculture, livestock and logging, among others. This work aimed to research about Brazilian environmental legislation with emphasis on the Forest Code in order to show the still existing gaps in the new legislation, analyzing how to use-occupation by the new consolidated environmental law and also propose sustainable activities that minimize negative impacts to these areas of paramount importance for the ecosystem balance. The results show gaps in the environmental legal protection, and the need to implement less impactful activities in these protected areas -APP and RL. The agroforestry system presented itself as an excellent alternative to the issues mentioned above because in addiction to protect, it also diversifies income to small farmers.